Alterations in Antioxidant Status and Erythrocyte Properties in Children with Autism Spectrum Disorder - Tomas Jasenovec; Dominika Radosinska; Katarina Jansakova; Maria Kopcikova; Aleksandra Tomova; Denisa Snurikova; Norbert Vrbjar; Jana Radosinska (MDPI AG, 2023)
Erythrocytes are responsible for the transport of oxygen within the organism, which is particularly important for nerve tissues. Erythrocyte quality has been shown to be deteriorated in oxidative stress conditions. In this study, we measured the same series of oxidative stress markers in plasma and erythrocytes to compare the differences between neurotypical children (controls) and children with autism spectrum disorder (ASD). We also focused on erythrocyte properties including their deformability, osmotic resistance, Na,K-ATPase activity, nitric oxide levels and free radical levels in children with ASD and controls. Greater oxidative damage to proteins and lipids was observed in the erythrocytes than in the plasma of ASD subjects. Additionally, antioxidant enzymes were more active in plasma samples from ASD children than in their erythrocytes. Significantly higher nitric oxide level and Na,K-ATPase enzyme activity were detected in erythrocytes of ASD individuals in comparison with the controls. Changes in oxidative status could at least partially contribute to the deterioration of erythrocyte morphology, as more frequent echinocyte formation was detected in ASD individuals. These alterations are most probably responsible for worsening the erythrocyte deformability observed in children with ASD. We can conclude that abnormalities in antioxidant status and erythrocyte properties could be involved in the pathomechanisms of ASD and eventually contribute to its clinical manifestations.